2017
DOI: 10.18632/oncotarget.18073
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of the PI3K/mTOR pathway prevent STAT5 phosphorylation inJAK2V617Fmutated cells through PP2A/CIP2A axis

Abstract: Inhibition of the constitutively activated JAK/STAT pathway in JAK2V617F mutated cells by the JAK1/JAK2 inhibitor ruxolitinib resulted in clinical benefits in patients with myeloproliferative neoplasms. However, evidence of disease-modifying effects remains scanty; furthermore, some patients do not respond adequately to ruxolitinib, or have transient responses, thus novel treatment strategies are needed. Here we demonstrate that ruxolitinib causes incomplete inhibition of STAT5 in JAK2V617F mutated cells due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…The BRD4/BET/NF-kB signaling pathway also has been suggested to contribute to MPN, as the addition of BET inhibitors to Jakinibs has been shown to markedly reduce serum levels of inflammatory cytokines, accompanied by reduction in disease burden, and reversal of bone marrow fibrosis in preclinical models (Kleppe et al, 2018). In addition, simultaneous inhibition of STAT5 phosphorylation on tyrosine and serine residues had synergistic effects against JAK2V617F mutant-positive cell lines, suggesting that approaches that target both post-translational modifications of STAT5 may be of benefit to patients with PMF (Bartalucci et al, 2017).…”
Section: G Janus Kinase/signal Transducer and Activator Of Transcripmentioning
confidence: 99%
“…The BRD4/BET/NF-kB signaling pathway also has been suggested to contribute to MPN, as the addition of BET inhibitors to Jakinibs has been shown to markedly reduce serum levels of inflammatory cytokines, accompanied by reduction in disease burden, and reversal of bone marrow fibrosis in preclinical models (Kleppe et al, 2018). In addition, simultaneous inhibition of STAT5 phosphorylation on tyrosine and serine residues had synergistic effects against JAK2V617F mutant-positive cell lines, suggesting that approaches that target both post-translational modifications of STAT5 may be of benefit to patients with PMF (Bartalucci et al, 2017).…”
Section: G Janus Kinase/signal Transducer and Activator Of Transcripmentioning
confidence: 99%
“…Targeting mTOR has also demonstrated positive anti-MPN effects as a single agent and in combination with JAK2 inhibition. 45,[65][66][67][68][69] The potency of the combination of INCB053914 and ruxolitinib was also manifested in in vivo MPN models driven by aberrant JAK2 signaling. The combination of INCB053914 and ruxolitinib antagonized the growth of SET2 cell xenograft tumors at doses of each drug that had little to no effect as monotherapies ( Figure 6A).…”
Section: Incb053914 and Ruxolitinib Suppress Jak2 V617f -Driven Tumormentioning
confidence: 99%
“…The mechanisms of CIP2A activation and overexpression in cancer cells have been investigated by several studies, in which some pathways were found to be associated with development of cancer, such as PI3K/mTOR and MAPK/ERK signaling pathway [27,35]. In the current study, we profiled the phosphokinase signaling pathways associated with CIP2A in different cell lines of CRC and found p-p53 (S392) and p-STAT5a (Y694) to be associated with the depletion of CIP2A expression.…”
Section: Discussionmentioning
confidence: 67%